Student activism and social networks: : Mobilization dynamics in the 2013 protests (Intercom - Brazilian Journal of Communication Sciences, 2026)
This article reports the partial results of the research project “Educational Dimensions of the 2013 Protests in Brazil,” focusing on a literature review of the use of conventional and new information and communication technologies in this cycle of protests. It analyzes the role of digital social networks in the mobilizations, highlighting student activism and the reconfiguration of public space. Based on 28 academic publications between 2013 and 2022, it examines how these platforms articulated, expressed, and gave visibility to the 2013 Journeys. In the analytical-interpretative approach, we find four axes: media conflict, network mobilization, symbolic youth protagonism, and crises of representation. These axes explain the constitution of political subjects and the organization of protests. The articulation of these categories proposes an interpretative model that highlights contemporary youth culture, marked by digital mediations, symbolic disputes, and decentralized collective action.
Keywords: youth; social networks; student activism; Journeys of 2013 protests; political mobilization.